Tax Factors, Audit Quality, and Multinationality in Transfer Pricing Practices of Multinational Firms - Ambarita, Dinar; Gibtiyyah, Riska Mariyatul; Ibrohim, Ibrohim (Journal of Law and Social Politics, 2024)
Background: Transfer pricing practices are widely used by multinational companies as a mechanism for tax management and profit allocation among related entities. Several factors, including tax burden, audit quality, and multinationality, are believed to influence transfer pricing decisions; however, empirical findings remain inconclusive, particularly in the context of multinational firms in Indonesia. Objective: This study aims to examine the effect of tax, audit quality, and multinationality on transfer pricing practices in multinational companies listed on the Indonesia Stock Exchange (IDX). Methods: This study employs a quantitative approach using panel data regression analysis. The sample consists of 19 multinational companies listed on the IDX during the 2018–2022 period, selected through purposive sampling. Secondary data were obtained from published corporate financial statements. Data analysis was conducted using EViews 10 Student Version Lite, and the most appropriate estimation model was determined prior to hypothesis testing. Results: The results indicate that the Fixed Effect Model (FEM) is the best model for this study. Partially, tax and audit quality have a significant effect on transfer pricing practices, while multinationality does not show a significant partial effect. Simultaneously, tax, audit quality, and multinationality jointly have a significant effect on transfer pricing. Conclusion: This study concludes that tax and audit quality are important determinants of transfer pricing practices among multinational companies in Indonesia. Although multinationality does not individually affect transfer pricing, the combined influence of all variables highlights the need for comprehensive monitoring of transfer pricing practices by companies and regulators.